2021
DOI: 10.1021/acs.inorgchem.1c02817
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Assembly of Tetrahedral Zr4(embonate)6 Cages with Eu3+ Ions

Abstract: Herein we systematically investigated the coordination assembly behavior of Zr4L6 cages with Eu3+ ions at room temperature. Through adjustment of the concentration of Eu salt and changes of the type and molar ratio of the solvent, a series of Zr4L6-Eu structures with different structure dimensionalities have been synthesized and structurally characterized. In addition, we also studied the optical properties of these materials in detail, including the fluorescent and third-order nonlinear-optical properties. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…[ 28‐34 ] By using the Zr 4 L 6 (L = embonate) tetrahedron as a reactive precursor to assembly with Eu 3+ ions, a series of novel cage‐based bimetallic Zr‐Eu complexes with various dimensional architectures were synthesized by two‐step reaction. [ 32 ] Interestingly, we found that a layer structure with π − π stacking forces between L ligands shows notable optical limiting effect. In fact, the rich naphthalene rings on its surface facilitate the formation of π − π stacking interactions, [ 29,33 ] so such a tetrahedral cage (including isostructural Ti 4 L 6 cage) is regarded as an excellent building block for the construction of cage‐based MOFs with third‐order nonlinear‐optical (NLO) properties.…”
Section: Background and Originality Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 28‐34 ] By using the Zr 4 L 6 (L = embonate) tetrahedron as a reactive precursor to assembly with Eu 3+ ions, a series of novel cage‐based bimetallic Zr‐Eu complexes with various dimensional architectures were synthesized by two‐step reaction. [ 32 ] Interestingly, we found that a layer structure with π − π stacking forces between L ligands shows notable optical limiting effect. In fact, the rich naphthalene rings on its surface facilitate the formation of π − π stacking interactions, [ 29,33 ] so such a tetrahedral cage (including isostructural Ti 4 L 6 cage) is regarded as an excellent building block for the construction of cage‐based MOFs with third‐order nonlinear‐optical (NLO) properties.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Recently, our synthetic strategy has been to replace the commonly used one‐step method with stepwise assembly strategy. [ 28‐34 ] By using the Zr 4 L 6 (L = embonate) tetrahedron as a reactive precursor to assembly with Eu 3+ ions, a series of novel cage‐based bimetallic Zr‐Eu complexes with various dimensional architectures were synthesized by two‐step reaction. [ 32 ] Interestingly, we found that a layer structure with π − π stacking forces between L ligands shows notable optical limiting effect.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Recently, the Ti 4 L 6 tetrahedron (MOC-25, Scheme 3) was applied as a cage-based ligand to connect metal ions into diverse structures by Chen, He, and co-workers. [41] MOC-25 is stable and soluble in many solvents and has uncoordinated carboxylate O atoms. Such anion cages can further be connected by Eu(III) or La(III) ions by adjusting the metal salt concentrations and the type and molar ratio of the solvent.…”
Section: Coordination-bond Linking Of Mocsmentioning
confidence: 99%
“…In 5 , MOC‐24 is connected by Ba 2+ cations to produce a pcu network (Figure 2b). Recently, the Ti 4 L 6 tetrahedron (MOC‐25, Scheme 3) was applied as a cage‐based ligand to connect metal ions into diverse structures by Chen, He, and co‐workers [41] . MOC‐25 is stable and soluble in many solvents and has uncoordinated carboxylate O atoms.…”
Section: Linking Of Mocs With Strong Interactionsmentioning
confidence: 99%
“…Recently, we have been devoted to the research work of multistage assembly. 32–34 By using the tetrahedral cage (Ti 4 L 6 or Zr 4 L 6 ) as a reactive precursor for assembly with metal ions or additional auxiliary ligands, 35,36 a series of advanced cage-based materials with various dimensional structures were obtained by a two-step reaction, including 3D frameworks (PTC-205 37 and PTC-220 38 ) with hydrocarbon sorption capacities, simple cage compounds (PTC-108 34 and PTC-201 39 ) with identification and separation functions, a series of co-crystals (PTC-231, 40 PTC-235 33 and PTC-296 41 ) with nonlinear optical effects, and so on. In fact, in such a tetrahedral cage as a special ligand for the construction of MOFs, its coordination-active vertices trap other metal ions, which often cannot meet the usual tetrahedral or octahedral coordination environment due to steric hindrance, endowing them with the possibility of coordinating one to four solvents.…”
mentioning
confidence: 99%